How Difficult is Claiming Knowledge? A Study from Cognitive Domain Perspective in Writing International Scientific Article - Azizah, Umu Arifatul; Tosriadi, Tosriadi (Bina Nusantara University, 2018)
This research examined and elaborated the challenges in claiming knowledge faced by students relating to writing in the international scientific article in English. The participants were 20 English master students from one of the universities in Indonesia. The researchers used a questionnaire to find out the coverage level of the difficulties regarding knowledge claim in writing for publication. The researchers also chose purposive sampling technique because the chosen respondents had the adequate experience in writing international scientific article. The researchers find that knowledge explication that considers the writer to use complex thinking is the most difficult stage of thinking in writing the international scientific article. Surprisingly, knowledge analysis is the easiest one for the participants. Despite this, the researchers hope that the findings lead to useful insight into how the students claim the knowledge well. Eventually, discovering the exact method to improve students’ competency in claiming knowledge will be the further study.